Helically chiral mixed-valence systems comprising N-heterotriangulenes: stabilization of the cationic species by π-Expansion - Borstelmann, Jan; Zank, Simon; Krug, Marcel; Berger, Georg; Fröhlich, Nina; Glotz, Gabriel; Gnannt, Frederik; Schneider, Lars; Rominger, Frank; Deschler, Felix; Clark, Timothy; Gescheidt, Georg; et al. (Angewandte Chemie. International edition, 2025)
We report the efficient stabilization of nitrogen-centered radical cations in a dimeric N-heterotriangulene bridged by a rigid π-conjugated [5]helicene backbone (NTH). The rigid scaffold exhibits helical chirality, allowing the enantiomers to be separated and their chiroptical properties studied, including circular dichroism (CD) and circularly polarized luminescence (CPL). Successive oxidation towards the radical cation NTH⋅+ and dication NTH2+ reveals strong electronic communication between the two nitrogen-centers, as demonstrated by X-ray crystallography, electrochemistry, UV/Vis/nIR spectroscopy and electron paramagnetic resonance (EPR) spectroscopy. CD measurements of the enantiomerically pure cations reveal strong Cotton effects in the nIR region extending up to 2000 nm. Density functional theory confirms the observed enhanced electronic communication, classifying NTH⋅+ as a Robin-Day Class III mixed-valence charge-transfer (MV-CT) system. NTH2+ exhibits a quinoidal structure with partial diradical character and open-shell singlet ground state, as shown by variable temperature EPR measurements. Time-resolved transient absorption spectroscopy shows the photo-induced generation of NTH⋅+ in the presence of a suitable electron acceptor.
Online veröffentlicht am 10. Februar 2025
Gesehen am 18.08.2025